Hobbes and the political economy of power - Donald Wittman (University of California, Economics Department, 2006)
This paper evaluates the sustainability of large current account imbalances in the era when the Chinese GDP growth rate and current account/GDP exceed 10%. We investigate the size distribution and the durability of current account deficits during 1966-2005, and report the results of a simulation that relies on the adding-up property of global current account balances. Excluding the US, we find that size does matter: the length of current account deficit spells is negatively related to the relative size of the countries' GDP. We conclude that the continuation of the fast growth rate of China, while maintaining its large current account/GPD surpluses, would be constrained by the limited sustainability of the larger current account deficits/GDP of courtiers that grow at a much slower rate. Consequently, short of the emergence of a new demander of last resort, the Chinese growth path would be challenged by its own success.
Keywords: F15; F21; F32; F43; 330; current account imbalances; growth; size; adding-up property; Leviathan-Modell; Public Choice; Diktatur; Demokratie; Macht; Anarchie; Theorie